Antimicrobial Resistance in Livestock: A Serious Threat to Public Health - Roberto Bava; Fabio Castagna; Carmine Lupia; Giusi Poerio; Giovanna Liguori; Renato Lombardi; Maria Diana Naturale; Caterina Mercuri; Rosa Maria Bulotta; Domenico Britti; Ernesto Palma (MDPI AG, 2024)
Antimicrobial resistance represents an alarming public health problem; its importance is related to the significant clinical implications (increased morbidity, mortality, disease duration, development of comorbidities, and epidemics), as well as its economic effects on the healthcare sector. In fact, therapeutic options are severely limited by the advent and spread of germs resistant to many antibiotics. The situation worldwide is worrying, especially in light of the prevalence of Gram-negative bacteria-Klebsiella pneumoniae and Acinetobacter baumannii-which are frequently isolated in hospital environments and, more specifically, in intensive care units. The problem is compounded by the ineffective treatment of infections by patients who often self-prescribe therapy. Resistant bacteria also show resistance to the latest generation antibiotics, such as carbapenems. In fact, superbacteria, grouped under the acronym extended-spectrum betalactamase (ESBL), are becoming common. Antibiotic resistance is also found in the livestock sector, with serious repercussions on animal production. In general, this phenomenon affects all members of the biosphere and can only be addressed by adopting a holistic "One Health" approach. In this literature overview, a stock is taken of what has been learned about antibiotic resistance, and suggestions are proposed to stem its advance.